Nikolay Volodos – endoprosthesis of aorta history - N. S. Yashchuk; B. V. Cherpak; I. O. Ditkivskyy; V. I. Kravchenko (Ukrainian Journal of Cardiovascular Surgery, 2016)
It is world known fact – first stent-graft was invented in 1985 in former Soviet Union in Kharkiv by Nikolay Volodos.